Utility of Xpert MTB/RIF Ultra and digital chest radiography for the diagnosis and treatment of TB in people living with HIV: a randomised controlled trial (XACT-TB). (13th August 2022) - Mukoka, Madalo; Twabi, Hussein H; Msefula, Chisomo; Semphere, Robina; Ndhlovu, Gabriel; Lipenga, Trancizeo; Sikwese, Tionge Daston; Malisita, Kenneth; Choko, Augustine; Corbett, Elizabeth L; MacPherson, Peter; Nliwasa, Marriott
Abstract: Background: TB is a leading cause of morbidity among HIV positive individuals. Accurate algorithms are needed to achieve early TB diagnosis and treatment. We investigated the use of Xpert MTB/RIF Ultra in combination with chest radiography for TB diagnosis in ambulatory HIV positive individuals. Methods: This was a randomised controlled trial with a 2-by-2 factorial design. Outpatient HIV clinic attendees with cough were randomised to four arms: Arm 1—Standard Xpert/no chest radiography (CXR); Arm 2—Standard Xpert/CXR; Arm 3—Xpert Ultra/no CXR; and Arm 4—Xpert Ultra/CXR. Participants were followed up at days 28 and 56 to assess for TB treatment initiation. Results: We randomised 640 participants. Bacteriologically confirmed TB treatment initiation at day 28 were: Arm 1 (8.4% [14/162]), Arm 2 (6.9% [11/159]), Arm 3 (8.2% [13/159]) and Arm 4 (5.6% [9/160]) and between Xpert Ultra group (Arms 3 and 4) (6.9% [22/319]) vs Standard Xpert group (Arms 1 and 2) (7.8% [25/321]), risk ratio 0.89 (95% CI 0.51 to 1.54). By day 56, there were also similar all-TB treatment initiations in the x-ray group (Arms 2 and 4) (16.0% [51/319]) compared with the no x-ray group (Arms 1 and 3) (13.1% [42/321]), risk ratio 1.22 (95% CI 0.84 to 1.78); however, the contribution of clinically diagnosed treatment initiations were higher in x-ray groups (50.9% vs 19.0%). Conclusions: Xpert Ultra performed similarly to Xpert MTB/RIF. X-rays are useful for TB screening but further research should investigate how to mitigate false-positive treatment initiations.